Pelatihan Pembukuan Keuangan Sederhana dalam Rangka Pelaksanaan Kebijakan Pajak yang Baru (PP Nomor: 23/2018) Untuk Pelaku UMKM Naik Kelas di Kota Depok - Notika Rahmi; Chairil Anwar Pohan; Pebriana Arimbhi; M Mansur; Zulkifli Zulkifli (Institut Ilmu Sosial dan Manajemen Stiami, 2020)
The existence of Micro, Small and Medium Enterprises (MSMEs) can no longer be doubted because they are proven to be able to survive and become the economic cogs. In 2011 MSMEs were able to contribute significantly to state revenue by contributing 61,9 percent of gross domestic product (GDP) revenue through tax payments. But the development of MSMEs in Indonesia is still very weak, one of the problems faced is human resources. MSMEs require targeted empowerment, guidance and development to be able to compete with large-scale companies. From the tax sector, the government has made special rules to facilitate MSMEs business people in their tax payments, namely through PP Number 23 of 2018. And furthermore it is expected that MSMEs business players can increase the level of making simple accounting which will help to tidy the administration of their businesses. In this case, we help MSMEs businesses to improve their capability and understanding in accounting and the new Tax Regulation (PP no.23/2018). This activity was attended by 51 MSMEs business people in the city of Depok. After attending the training, participants were given the opportunity to ask questions and consult. The results of the training and mentoring show an increase in knowledge about simple accounting that can be made by the participants themselves and participants become aware of the new taxation rules namely PP No.23 of 2018 as well as raising awareness about the importance of paying taxes.